Identification and Characterization of TF-lncRNA Regulatory Networks Involved in the Tumorigenesis and Development of Adamantinomatous Craniopharyngioma - Xu, Dingkang; Guo, Yufeng; Lei, Shixiong; Guo, Abao; Song, Dengpan; Gao, Qiang; Zhao, Shengqi; Yin, Kaiwen; Wei, Qingjie; Zhang, Longxiao; Wang, Xiaoxuan; Wang, Jie; et al. (Frontiers in Oncology, 2022)
Craniopharyngiomas (CPs) are rare tumors arising from the sellar region. Although the best outcome of one subtype, adamantinomatous craniopharyngiomas (ACPs), is obtained by gross total resection, little is known about the role of long noncoding RNAs (LncRNAs) and transcription factors (TFs) in ACP tumorigenesis. . In total, 12 human ACP and 5 control samples were subjected to transcriptome level sequencing. We built an integrated algorithm for identifying lncRNA and transcription factor regulators of the CP-related pathway. Further, ChIP-Seq datasets with binding domain information were used to further verify and identify the TF-LncRNA correlation. RT-PCR and immunohistochemistry staining were applied in the validation of potential targets. 5 pathways associated with ACP were identified and defined by an extensive literature search. Based on the specific pathways and the whole gene expression profile, 266 ACP-related LncRNAs and 39 TFs were calculated by our integrating algorithm. Comprehensive analysis of ChIP-Seq datasets revealed that 29 TFs were targeted by 12000 LncRNAs from a wide range of tissues including 161 ACP-related LncRNAs identified by the computational method. These 29 TFs and 161 LncRNAs constituting 1004 TF-LncRNA pairs played role in the different ACP-related pathways as potential regulators. 232 TF-LncRNA network were consequently established based on the differential gene expression. Validation using RT-PCR and immunohistochemistry staining revealed positive expression of the ACP-related TFs, E2F2 and KLF5, in ACP. Moreover, the level of LncRNA RP11-360P21.2 was increased in ACP tissues. In this study, we introduced an integrated algorithm for identifying LncRNA and TF regulators of ACP-related pathway. This is the first comprehensive study to investigate the potential TF and LncRNA regulatory network in ACP with the systematical method. The resulting data serve as a valuable resource for understanding underlying mechanisms in ACP-related LncRNAs and TFs.